Framework material containing elements easy to burn out and preparation method thereof

By adding Fe, Mg, P, Zn and Sn elements to C19400 alloy and adopting a specific process flow, the shortcomings of existing materials in high strength and conductivity are solved, and the yield and material performance are improved.

CN119464824APending Publication Date: 2025-02-18CHINALCO DAYE COPPER PLATE & STRIP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411483349.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing C19400 alloy materials have shortcomings in terms of high strength and electrical conductivity, and the addition of burn-in elements will lead to increased casting difficulty and low yield.

Method used

By adding appropriate amounts of Fe, Mg, P, Zn and Sn elements to the C19400 alloy and using specific smelting, casting and heat treatment processes, the composition and structure of the material are optimized to improve the overall performance of the material.

Benefits of technology

The tensile strength, yield strength, corrosion resistance, hardness and softening temperature of the frame material are significantly improved, the burn rate of the burn-in element is reduced, and the yield rate and the overall performance of the material are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464824A_ABST
    Figure CN119464824A_ABST
Patent Text Reader

Abstract

The invention provides a framework material containing elements easy to burn out and a preparation method of the framework material. The frame material is prepared from the following components in percentage by mass: 2.1 to 2.3 percent of Fe, 0.085 to 0.15 percent of Mg, 0.015 to 0.05 percent of P, 0.05 to 0.1 percent of Zn, 0.01 to 0.04 percent of Sn and the balance of Cu and other inevitable impurities. The content of the impurities is lower than 0.04%. The framework material is prepared by the following steps: S1, preparing raw materials according to the mass percent of the components; s2, mixing the raw materials to prepare a melt; s3, casting the melt to obtain a frame material casting blank; and S4, the casting blank is subjected to a heat treatment process, and the frame material is obtained. Through reasonable matching of the components, the burn-out rate of elements easy to burn out is reduced, and the stability of the overall components of the frame material is also ensured. By optimizing the processing technology, the cast ingot with excellent surface quality is obtained, the internal quality of the cast ingot is also improved, and meanwhile, the cracking problem is also avoided, so that the high-strength and high-conductivity framework material containing elements easy to burn out is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of copper material processing, in particular to a frame material containing easily burnable elements and a preparation method thereof. Background Art

[0002] Driven by 5G technology, power and electronic equipment are gradually being integrated, miniaturized, and arranged in a high-density layout. This change has prompted the evolution of internal electronic supports towards thinner, stronger, and more efficient heat transfer, which has put forward higher requirements on the performance of copper alloys, while requiring lower production costs. Therefore, copper alloy products used in industries such as communications and mobile phones must be upgraded to high performance. The lead frame of an integrated circuit (IC) is a key component for supporting the chip and transmitting electrical signals, as well as a medium for dissipating heat. Its importance is self-evident. As IC technology moves towards higher density, smaller size, and more multifunctionality, the demand standards for lead frames and their electronic packaging materials are also constantly improving, requiring higher mechanical strength, electrical conductivity, and thermal conductivity, and these factors are mutually restrictive.

[0003] In the preparation of frame materials, the most mature application is C19400 alloy. However, the strength of ordinary C19400 lead frame materials is not high, and it is very easy to have hot rolling cracking problems, which seriously affects the service life of subsequent products. In view of the limitations of existing C19400 alloy materials in the above aspects, researchers are actively exploring ways to improve them. At present, the existing technology considers introducing other substances on the basis of C19400 alloy, such as rare earth elements, trace elements or alloy materials, etc., in order to meet the current high-strength frame structural parts for conductivity, heat dissipation and softening resistance. The stringent requirements, thereby preparing a higher strength frame material without affecting the conductivity of the alloy.

[0004] However, since some metals are easily burnt elements, such as Mg, Zn, etc., the addition of these elements will increase the difficulty of casting the frame material, cause serious burnout, increase the difficulty of processing, and thus seriously affect the yield of the product. Based on this, it is urgent to develop a frame material containing easily burnt elements and a preparation method thereof to solve the problems existing in the existing foundation. Summary of the invention

[0005] In view of this, the present invention proposes a frame material containing easily burnt elements and a preparation method thereof, so as to solve the problems in the prior art of severe burning of the frame material due to excessive magnesium content, casting cracking, and low yield caused by subsequent ingot processing cracking.

[0006] On the one hand, the present application provides a frame material containing easily burnt elements, wherein the frame material, by mass percentage, includes the following components: Fe 2.1-2.3%, Mg 0.085-0.15%, P 0.015-0.05%, Zn 0.05-0.1%, Sn 0.01-0.04%, and the remainder is Cu and other unavoidable impurities; the content of the impurities is less than 0.04%.

[0007] By adopting the above technical solution, adding appropriate amounts of iron, magnesium, phosphorus, zinc, tin and other elements to the frame elements that are easily burned can significantly improve the comprehensive performance of the frame material, including but not limited to: tensile strength, yield strength, corrosion resistance, hardness and softening temperature.

[0008] On the basis of the above technical solution, preferably, the frame material comprises the following components, by mass percentage: Fe 2.1-2.3%, Mg 0.09-0.12%, P 0.015-0.05%, Zn 0.05-0.1%, Sn 0.01-0.04%, and the remainder is Cu and other inevitable impurities; the content of the impurities is less than 0.04%.

[0009] By adopting the above technical scheme, magnesium is an element that is easily burned, and excessive addition of it will lead to the risk of significantly reduced conductivity, and the plasticity and toughness of the frame material will also be reduced, while increasing the difficulty of casting. In addition, it will also destroy the balance of other elements in the alloy, thereby affecting the overall performance of the alloy; if the magnesium content is added too little, the improvement effect on the alloy is not obvious enough, especially the improvement effect on the strength is not obvious; the present invention further controls the Mg content to 0.09-0.12% through experiments, which can give full play to its improvement effect on the alloy and further improve the comprehensive performance of the frame material.

[0010] On the other hand, the present application also relates to a method for preparing the above-mentioned frame material, the method comprising the following steps:

[0011] S1. Prepare raw materials according to the mass percentage of the components, wherein the raw materials include: C19400 alloy waste material, CuP master alloy, CuMg master alloy, CuFe master alloy, pure Zn and pure Sn;

[0012] S2, sequentially mixing and smelting C19400 alloy waste material, pure Sn and CuFe master alloy, and after Fe and Sn reach the mass percentage, keeping warm, slagging, and then sequentially adding pure Zn, CuP master alloy and CuMg master alloy, and standing to obtain a melt whose components all meet the mass percentage;

[0013] S3, casting the melt of step S2 to obtain a frame material ingot;

[0014] S4, the frame material ingot of step S3 is heated, hot rolled, quenched, milled, rough rolled, first aging, intermediate rolled, second aging, finish rolled, stress relief annealed and straightened in sequence to obtain the frame material.

[0015] By adopting the above technical solution, firstly, using C19400 alloy waste as one of the raw materials can help reduce the production cost of frame materials and realize the recycling of resources; in addition, preparing the raw materials according to the mass percentage of each component can ensure the consistency of the performance of each batch of materials, thereby reducing the scrap rate and improving production efficiency. The use of CuMg master alloy, CuFe master alloy and CuP master alloy to introduce the three elements of magnesium, iron and phosphorus can significantly reduce the burn-out rate of metal elements, and can make them more evenly distributed in the base metal, improve the actual utilization rate of metal elements, and simplify the production process; in addition, by adding master alloys, it is not only easy to control and adjust the content of metal elements, but also can improve the processing performance of frame materials as a whole and extend their service life.

[0016] Secondly, the distributed smelting method is adopted to preferentially smelt Sn and CuFe intermediate alloys, which can not only ensure that the iron element can be fully melted and evenly distributed in the melt, reducing the element burnout caused by the difference in melting points, but also form a stable phase in the melt, avoiding the enrichment of Fe elements and the component segregation caused by the enrichment of large pieces of iron elements in the subsequent casting process, and also provide a better uniform distribution basis for the subsequent addition of zinc, phosphorus, and magnesium elements; and the orderly addition sequence can also reduce the segregation phenomenon between elements, thereby improving production efficiency and ensuring product quality. At the same time, during the smelting process, heat preservation and slag removal operations can effectively remove impurities and oxides in the melt, avoid further agglomeration of copper and reduce the casting receipt rate, provide a cleaner smelting environment for other elements added later, and effectively reduce the element burnout.

[0017] Finally, by precisely controlling the heat treatment process, precise processing and other methods, the material production process is further optimized, thereby effectively improving production efficiency and product quality, so that the prepared frame material can meet the strict requirements of applications in the electronics and communications fields.

[0018] Furthermore, in S1, the CuFe master alloy is CuFe15, the CuP master alloy is CuP14, and the CuMg master alloy is CuMg25.

[0019] By adopting the above technical solution, the intermediate alloy material used in the present invention can be any material that meets the composition. The present invention recommends the use of commercially available CuFe15, CuP14 and CuMg25 as intermediate alloys, which has multiple advantages in the preparation of easy-to-burn frame materials, such as precise control of element content, improved alloy performance, optimized production process, and improved yield and quality stability. These advantages make the prepared frame material have a wider application prospect and higher competitiveness in the fields of electronic equipment, communication equipment, etc.

[0020] Furthermore, in S2, the standing time is 15 to 20 minutes.

[0021] By adopting the above technical solution, it is ensured that there is enough time for the gas in the melt to be discharged as much as possible, and the operator has time to carry out the next operation without affecting the overall production efficiency.

[0022] Furthermore, in S3, the casting temperature is 1180-1210° C., and the casting speed is 55-65 mm / min.

[0023] By adopting the above technical scheme, it is ensured that the melt can be further exhausted. Too high a temperature is likely to cause the melt to inhale air, and too low a temperature is likely to cause insufficient fluidity of the copper liquid, resulting in casting difficulties. Therefore, it is appropriate to control the casting temperature at 1180-1210°C. The appropriate casting speed can not only obtain a shallow liquid cavity, which is conducive to the discharge of gas and the floating of slag, reducing casting defects, but also ensure production efficiency and the surface quality of the billet. Too low a casting speed will result in fewer casting defects, but the surface quality of the billet will be poor and casting will be difficult. Too high a casting speed will result in a deeper liquid cavity, so that the gas is not easy to discharge and the slag is not easy to float, resulting in less internal quality and more defects such as pores and looseness.

[0024] Furthermore, during the casting process, the vibration frequency is 30 to 40 times / min, the slag removal frequency is 2 to 3 times / 10 min, and the ash covering thickness is 80 to 100 mm.

[0025] By adopting the above technical scheme, during the casting process, vibration not only helps the liquid metal to flow more evenly in the mold, reduces the generation of bubbles and inclusions, and improves the quality of the casting, but also helps the liquid metal to fill the mold better and reduce shrinkage and shrinkage caused by cooling shrinkage; the appropriate vibration frequency can promote the crystallization process of the liquid metal, refine the grain structure, and thus improve the mechanical properties and corrosion resistance of the casting. Regular slag removal can timely remove impurities and oxides in the melt, maintain the cleanliness of the melt, and improve the quality of the casting. Through a reasonable slag removal frequency, while ensuring the quality of the casting, it can avoid excessive slag removal. Waste of materials and increased costs. Ash covering the surface of the melt can play a certain role in heat preservation, reduce the heat loss of the melt, and is conducive to the homogenization and stabilization of the melt. At the same time, the covering layer can reduce the contact area between the melt and the air, reduce the oxidation rate of the melt, and protect the chemical composition and physical properties of the melt; in addition, ash covering can also effectively reduce the pollution of the workshop environment by smoke and harmful gases generated during the smelting process, and improve the working environment of workers.

[0026] In the casting process of the present invention, the molten metal is easily cooled in the device and forms a shell. If the device does not contain a vibrating part, the shell may adhere to the inner wall of the crystallizer. When the shell moves downward with the ingot, it is easy to cause the shell to tear, resulting in defects on the surface of the ingot. And vibration helps the newly formed shell to move relative to the inner wall of the device, which can reduce the friction between the shell and the device, making it easier for the shell to detach from the inner wall of the device. By this means, cracks, segregation and other defects on the surface of the ingot can be reduced, and the surface quality of the ingot can be improved. In addition, the casting process can be made smoother, thereby increasing the casting speed and increasing production efficiency. And vibration can also help the gas in the liquid cavity to be discharged smoothly, reducing the formation of defects such as pores. However, too slow or too fast cannot achieve the best casting effect.

[0027] In the casting process of the present invention, due to the addition of easily oxidizable elements such as Mg and Zn, slagging is likely to occur during the casting process. If it is not removed, it will affect the casting quality and surface quality of the casting, causing the ingot to crack during the drawing process. If the frequency is too fast, it will easily lead to the aspiration of the melt and the number of workers' operations, increasing the labor intensity. If the frequency is too slow, it will easily affect the surface quality of the drawing, thereby affecting the internal and external surface quality of the ingot.

[0028] In the casting process of the present invention, the purpose of ash covering is to maintain the quality of the melt and prevent the melt from being oxidized and inhaled. If the thickness of the ash covering is too low, the covering effect will not be achieved, and the problems of melt oxidation and inhalation will still occur, thereby affecting the uniformity of the composition of the ingot. If the thickness of the ash covering is too high, it will affect the discharge of gas in the melt, which is not conducive to the smooth discharge of gas, resulting in inclusions, looseness and other problems inside the ingot, and also increasing the labor intensity of workers.

[0029] Furthermore, in S4, the heating temperature of the ingot is 930-960° C., and the ingot is kept warm for 5-6 hours after being heated.

[0030] By adopting the above technical solution, these elements are redistributed by heating at a changed heating temperature and processing time, thereby reducing or eliminating segregation; it helps to improve the uniformity of the microstructure of the ingot, reduce the non-uniformity of grain size and shape, thereby improving the overall performance of the material. It also reduces internal stress and avoids cracking during hot rolling; at the same time, internal defects and stress are reduced, which helps to improve the overall performance of the alloy.

[0031] Furthermore, in S4, the hot rolling passes are 7 to 9, and the final rolling temperature is 730 to 750°C.

[0032] By adopting the above technical scheme and optimizing the hot rolling passes reasonably, the coarse grains in the ingot can be effectively broken up, and the grain refinement can be promoted, thereby improving the mechanical properties and processing properties of the material. At the same time, the casting defects such as pores, shrinkage cavities, cracks in the ingot can be compacted or welded, thereby improving the integrity and reliability of the material. It further contributes to the uniform distribution of the components and reduces the segregation phenomenon. By controlling the temperature, rolling speed and reduction of hot rolling, the mechanical properties and microstructure of the material can be adjusted to meet the needs of different applications. The final rolling temperature affects the final organizational structure of the material, and the appropriate final rolling temperature can obtain the required mechanical properties and microstructure. It can avoid excessive hardening of the material at low temperature, reduce the difficulty of deformation and equipment load. It helps to inhibit the excessive growth of grains and maintain a fine and uniform grain structure. Provide suitable starting conditions for subsequent heat treatment or cooling processes to ensure the performance of the final product.

[0033] Furthermore, in S4, the rough rolling passes are provided with 9 passes, and the total deformation amount is 88-92%.

[0034] By adopting the above technical scheme, multiple rolling can make the internal structure of the material more uniform, reduce component segregation and internal defects, and by controlling the total deformation during the rough rolling process, it is beneficial to the smooth progress of subsequent processing (such as intermediate rolling, finishing rolling, and aging treatment), thereby improving the overall quality of the material.

[0035] The frame material containing easily burnable elements provided by the present invention has the following beneficial effects compared with the prior art:

[0036] The present invention not only significantly reduces the burnout rate of easily burnt elements such as Zn and Mg, but also ensures the stability of the overall composition of the frame material by rationally matching Fe, Mg, P, Zn and Sn elements, and adopting orderly addition and effective treatment processes. In addition, by optimizing the smelting, casting and processing processes, not only an ingot with excellent surface quality is obtained, but also its internal quality is improved, ensuring that the zinc and magnesium content of the entire ingot is uniform and consistent, and there is no component deviation at the head and tail. At the same time, this method also effectively avoids the cracking problem during hot rolling and cold rolling, thereby successfully preparing a frame material containing easily burnt elements with both high strength and high conductivity. Compared with the existing methods, the present invention not only reduces the burnout rate of the product and improves the yield rate, but also brings significant economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0038] Figure 1 This is a schematic diagram of a casting of a frame material containing an element that is easily burnt in Example 1 of the present invention;

[0039] Figure 2 Schematic diagram of the casting of the frame material containing the easily burnable element in Comparative Example 4 of the present invention. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] The present invention is further described below in conjunction with specific examples, and the protection scope of the present invention is not limited by the following examples. The sources of materials mainly involved in the examples are all conventional commercial products.

[0042] Example 1

[0043] The frame material containing the easily burnable element of this embodiment has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0044] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0045] S2, sequentially mix and smelt C19400 alloy waste material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 15 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0046] S3, casting the melt of S2, setting the casting temperature to 1210°C, the casting speed to 58mm / min, the slag removal frequency to 2 times / 10min, the vibration frequency to 30 times / min, the ash covering thickness to 90mm, to obtain a frame material casting blank;

[0047] S4, heating the frame material ingot of S3 to 930°C, keeping the temperature for 5 hours, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0048] Among them, the hot rolling passes are set to 7 passes, the final rolling temperature is 730°C, the rough rolling passes are set to 9 passes, and the total deformation is 88%.

[0049] Example 2

[0050] The frame material containing the easily burnable element of this embodiment has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0051] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0052] S2, sequentially mix and smelt C19400 alloy old material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 17 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0053] S3, casting the melt of S2, setting the casting temperature to 1180°C, the casting speed to 60 mm / min, the slag removal frequency to 3 times / 10 min, the vibration frequency to 33 times / min, the ash covering thickness to 80 mm, to obtain a frame material casting blank;

[0054] S4, heating the frame material ingot of S3 to 950°C, keeping the temperature for 6 hours, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0055] Among them, the hot rolling passes are set to 7 passes, the final rolling temperature is 735°C, the rough rolling passes are set to 9 passes, and the total deformation is 89%.

[0056] Example 3

[0057] The frame material containing the easily burnable element of this embodiment has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0058] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0059] S2, sequentially mix and smelt C19400 alloy waste material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 18 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0060] S3, casting the qualified melt of S2, setting the casting temperature to 1200°C, the casting speed to 55mm / min, the slag removal frequency to 3 times / 10min, the vibration frequency to 40 times / min, the ash covering thickness to 100mm, to obtain a frame material casting blank;

[0061] S4, heating the frame material ingot of S3 to 960°C, keeping the temperature for 5.4h, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0062] Among them, the hot rolling passes are arranged to be 9 passes, the final rolling temperature is 740°C, the rough rolling passes are arranged to be 9 passes, and the total deformation amount is 92%.

[0063] Example 4

[0064] The frame material containing the easily burnable element of this embodiment has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0065] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0066] S2, sequentially mixing and smelting C19400 alloy old material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, heat preservation, slag removal, and then sequentially adding pure Zn, CuP14 and CuMg25, standing for 20 minutes, to obtain a melt in which the contents of each component meet the mass percentage requirements;

[0067] S3, casting the qualified melt of S2, setting the casting temperature to 1190°C, the casting speed to 65mm / min, the slag removal frequency to 2 times / 10min, the vibration frequency to 35 times / min, the ash covering thickness to 90mm, and obtaining a frame material casting blank;

[0068] S4, heating the frame material ingot of S3 to 940°C, keeping the temperature for 5.5h, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0069] Among them, the hot rolling passes are arranged to be 9, the final rolling temperature is 745°C, the rough rolling passes are arranged to be 9, and the total deformation amount is 88%.

[0070] Example 5

[0071] The frame material containing the easily burnable element of this embodiment has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0072] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0073] S2, sequentially mix and smelt C19400 alloy waste material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 18 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0074] S3, casting the qualified melt of S2, setting the casting temperature to 1200°C, the casting speed to 60mm / min, the slag removal frequency to 2 times / 10min, the vibration frequency to 35 times / min, the ash covering thickness to 90mm, to obtain a frame material casting blank;

[0075] S4, heating the frame material ingot of S3 to 945°C, keeping the temperature for 5 hours, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0076] Among them, the hot rolling passes are arranged to be 8, the final rolling temperature is 750°C, the rough rolling passes are arranged to be 9, and the total deformation amount is 90%.

[0077] Comparative Example 1

[0078] The difference from Example 1 is that in S1, non-alloy material is used; the rest remains unchanged.

[0079] Comparative Example 2

[0080] The difference from Example 2 is that in S2, the order of adding materials is to mix and smelt C19400 alloy old material, pure Zn, CuP14 and CuMg25 in sequence. After the components are qualified, they are kept warm, slag is removed, and pure Sn and CuFe15 are added in sequence, and the rest remain unchanged.

[0081] Comparative Example 3

[0082] The difference from Example 3 is that in S3, the slag removal frequency is 4 times / 10 min, and the rest remains unchanged.

[0083] Comparative Example 4

[0084] The frame material containing the easily burnable element in this comparative example has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0085] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0086] S2, sequentially mix and smelt C19400 alloy old material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 14 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0087] S3, casting the qualified melt of S2, setting the casting temperature to 1170°C, the casting speed to 70mm / min, the slag removal frequency to 1 time / 10min, the vibration frequency to 28 times / min, the ash covering thickness to 75mm, and obtaining a frame material casting blank;

[0088] S4, heating the frame material ingot of S3 to 920°C, keeping the temperature for 7 hours, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0089] Among them, the hot rolling passes are set to 7 passes, the final rolling temperature is 720°C, the rough rolling passes are set to 9 passes, and the total deformation is 85%.

[0090] Comparative Example 5

[0091] The frame material containing the easily burnable element in this comparative example has the mass percentage of each component as shown in Table 1 below. The frame material is prepared by the following steps:

[0092] S1. Prepare raw materials according to the mass percentage of the components, including: C19400 alloy waste material, CuP14, CuMg25, CuFe15 and pure Zn and pure Sn;

[0093] S2, sequentially mix and smelt C19400 alloy old material, pure Sn and CuFe15, and after the contents of Fe and Sn components meet the mass percentage of the components, keep warm, remove slag, and then add pure Zn, CuP14 and CuMg25 in turn, let stand for 25 minutes, and obtain a melt in which the contents of each component meet the mass percentage requirements;

[0094] S3, casting the qualified melt of S2, setting the casting temperature to 1220°C, the casting speed to 50 mm / min, the slag removal frequency to 4 times / 10 min, the vibration frequency to 42 times / min, the ash covering thickness to 105 mm, and obtaining a frame material casting blank;

[0095] S4, heating the frame material ingot of S3 to 970°C, keeping the temperature for 4 hours, and then sequentially performing hot rolling, quenching, milling, rough rolling, primary aging, intermediate rolling, secondary aging, finishing rolling, stress relief annealing and straightening to obtain the frame material;

[0096] Among them, the hot rolling passes are arranged to be 9, the final rolling temperature is 760°C, the rough rolling passes are arranged to be 9, and the total deformation amount is 95%.

[0097] The mass percentages of the components of the frame materials prepared in Examples 1 to 5 and Comparative Examples 1 to 5 are shown in Table 1 below.

[0098] Table 1 Mass percentage of each component

[0099]

[0100] The inventors conducted the following performance tests on the frame materials prepared in the above embodiments and comparative examples, including:

[0101] 1) Tensile strength test

[0102] The test was carried out on an electronic universal mechanical properties testing machine in accordance with GB / T 228.1-2021 Tensile tests on metallic materials Part 1: Room temperature test method.

[0103] 2) Conductivity test

[0104] According to GB / T 32791-2016 standard, the copper strip is tested using an electric bridge.

[0105] 3) Vickers hardness test

[0106] According to the national standard GBT4340, the Vickers hardness of copper is measured on the HVS-1000Z automatic turret digital microhardness tester.

[0107] 4) Anti-softening temperature test

[0108] According to the national standard GB / T 33370-201, the Vickers hardness value of the strip is measured after treatment at different temperatures to obtain the corresponding anti-softening temperature.

[0109] 5) Number of defects and overall yield rate

[0110] Ultrasonic testing equipment is used to detect defects in ingots with a size greater than 1mm; the comprehensive yield rate is mainly calculated based on the actual production of the enterprise.

[0111] The above test results are recorded in Table 2 below.

[0112] Table 2 Performance test results

[0113]

[0114] Through the performance test results in Table 2, combined with the above embodiments and comparative examples, it can be concluded that:

[0115] (1) The tensile strength of the frame material prepared in the embodiment of the present invention is between 500 and 550 MPa, while the tensile strength of the comparative example is between 440 and 540 MPa, which is lower overall. This is because the change in tensile strength is mainly related to the microstructure and composition of the material. The embodiment makes the internal structure of the material more uniform and the grains are refined through strict smelting, casting and heat treatment processes, thereby improving the tensile strength. However, due to the different process parameters (such as casting temperature, standing time, etc.) of the comparative example, there may be larger grains or uneven distribution inside the material, which in turn affects the tensile strength.

[0116] (2) The conductivity of the frame material prepared in the embodiment of the present invention is between 62% IACS and 70% IACS, while the conductivity of the comparative example is between 56% IACS and 64% IACS, which is lower overall. This is because the change in conductivity is mainly related to the impurity content in the material. In the embodiment, the content of impurity elements is reduced through reasonable component ratio and purification process, thereby improving the conductivity. The comparative example has a high content of impurity elements due to improper component ratio or insufficient purification, which reduces the conductivity.

[0117] (3) The Vickers hardness of the frame material prepared in the embodiment of the present invention is between 150Hv and 155Hv, while the Vickers hardness of the comparative example is between 138Hv and 153Hv, which is lower overall. This is because the change in Vickers hardness is closely related to the heat treatment process of the material. The embodiment achieves a higher hardness by optimizing the heat treatment process (such as heating temperature and holding time). The comparative example has a less than ideal hardness of the material due to the different heat treatment processes.

[0118] (4) The softening resistance temperature of the frame material prepared in the embodiment of the present invention is between 470 and 475°C, while the softening resistance temperature of the comparative example is between 410 and 470°C, which is lower overall. The softening resistance temperature reflects the stability of the material at high temperatures. The embodiment improves the stability of the material at high temperatures by controlling the alloy composition and heat treatment process. The comparative example is more easily softened at high temperatures due to differences in composition or process.

[0119] (5) The number of defects in the frame material prepared in the embodiment of the present invention is 0, and the comprehensive yield rate is between 60% and 64%; while the number of defects in the comparative example is between 2 and 8, and the comprehensive yield rate is between 30% and 58%. It can be seen that the change in the number of defects is mainly related to the slag removal frequency, vibration frequency, ash coverage thickness, etc. during the casting process. The embodiment reduces the defects in the material and improves the yield rate through appropriate slag removal, vibration frequency, and ash coverage thickness. However, due to improper slag removal frequency or vibration frequency, the comparative example has more defects in the material and a lower yield rate.

[0120] The inventor takes Example 1 as an example, and the obtained casting billet has good surface quality and good forming performance. Figure 1 shown. Figure 2 The ingot obtained in Comparative Example 4 has severe surface cracks and poor internal quality, which seriously affects the subsequent processability of the strip.

[0121] In summary, the embodiments of the present invention effectively improve the microstructure and mechanical properties of the material by optimizing the composition ratio, smelting process, casting process and heat treatment process. However, the comparative example has a decrease in material properties due to the lack of certain process steps or improper parameter adjustment. Through the coordinated control of each stage of the present invention, an alloy strip with high yield of easily oxidizable elements, uniform composition, excellent surface quality and high yield can be prepared.

[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A frame material containing an element that is easily burnt, characterized in that: The frame material comprises the following components by mass percentage: Fe 2.1-2.3%, Mg 0.085-0.15%, P 0.015-0.05%, Zn 0.05-0.1%, Sn 0.01-0.04%, and the remainder is Cu and other inevitable impurities; the content of the impurities is less than 0.04%.

2. The frame material according to claim 1, characterized in that: The frame material comprises the following components by mass percentage: Fe 2.1-2.3%, Mg 0.09-0.12%, P 0.015-0.05%, Zn 0.05-0.1%, Sn 0.01-0.04%, and the remainder is Cu and other inevitable impurities; the content of the impurities is less than 0.04%.

3. A method for preparing the frame material according to claim 1 or 2, characterized in that: The method comprises the following steps: S1. Prepare raw materials according to the mass percentage of the components, wherein the raw materials include: C19400 alloy waste material, CuP master alloy, CuMg master alloy, CuFe master alloy, pure Zn and pure Sn; S2, sequentially mixing and smelting C19400 alloy waste material, pure Sn and CuFe master alloy, and after Fe and Sn reach the mass percentage, keeping warm, slagging, and then sequentially adding pure Zn, CuP master alloy and CuMg master alloy, and standing to obtain a melt whose components all meet the mass percentage; S3, casting the melt of step S2 to obtain a frame material ingot; S4, the frame material ingot of step S3 is heated, hot rolled, quenched, milled, rough rolled, first aging, intermediate rolled, second aging, finish rolled, stress relief annealed and straightened in sequence to obtain the frame material.

4. The method according to claim 3, characterized in that In step S1, the CuFe master alloy is CuFe15, the CuP master alloy is CuP14, and the CuMg master alloy is CuMg25.

5. The method according to claim 3, characterized in that In step S2, the standing time is 15 to 20 minutes.

6. The method according to claim 3, characterized in that In step S3, the casting temperature is 1180-1210° C., and the casting speed is 55-65 mm / min.

7. The method according to claim 6, characterized in that In the casting process, the vibration frequency is 30 to 40 times / min, the slag removal frequency is 2 to 3 times / 10min, and the ash covering thickness is 80 to 100 mm.

8. The method according to claim 3, characterized in that In step S4, the heating temperature of the ingot is 930-960° C., and the ingot is kept warm for 5-6 hours after being heated.

9. The method according to claim 3, characterized in that In step S4, the hot rolling passes are 7 to 9, and the final rolling temperature is 730 to 750°C.

10. The method according to claim 3, characterized in that In step S4, the rough rolling passes are provided with 9 passes, and the total deformation amount is 88-92%.